1988
DOI: 10.1136/ard.47.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Value of joint scintigraphy in the prediction of erosiveness in early rheumatoid arthritis.

Abstract: SUMMARY The value of scintigraphy in predicting development of new erosions in small peripheral joints was studied by visual evaluation of scintigrams and by three computerised methods. In 13 patients with newly diagnosed rheumatoid arthritis a total of 387 joints were examined clinically, scintigraphically, and radiographically. The follow up period was 24 months. Four eroded joints in three patients were found at the onset. Of the joints which were to become eroded, 46/47 were scintigraphically active at all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 18 publications
0
17
0
2
Order By: Relevance
“…Finding solutions to these problems will require the investigation and development of other modalities that will provide a more accurate evaluation of the actual pathologic change(s) involved. For example, bone scintigraphy will demonstrate active joints and will predict which joints will become eroded and which ones will not (20). As magnetic resonance imaging (MRI) continues to develop, our expertise and interpretation of MRI will also improve.…”
Section: Clinical and Pathophysiologic Variablesmentioning
confidence: 99%
“…Finding solutions to these problems will require the investigation and development of other modalities that will provide a more accurate evaluation of the actual pathologic change(s) involved. For example, bone scintigraphy will demonstrate active joints and will predict which joints will become eroded and which ones will not (20). As magnetic resonance imaging (MRI) continues to develop, our expertise and interpretation of MRI will also improve.…”
Section: Clinical and Pathophysiologic Variablesmentioning
confidence: 99%
“…Having evaluated the extent of bone-marrow edema with MRI of the hand, wrist, and feet in a 2-year study, Hetland et al considered this index Möttönen et al demonstrated a correlation between high scintigraphic activity and subsequent erosiveness. Their findings also suggested that erosions do not evolve in scintigraphically inactive joints [19].…”
Section: Discussionmentioning
confidence: 96%
“…New erosions were especially prone to appear in joints with persisting and high scintigraphic activity. On the other hand, repeatedly scanned but inactive joints never eroded [17].…”
Section: The Classic Bone Scan Using 99m-tc-phosphate Complexesmentioning
confidence: 95%